Haemosporidian parasites prevalence associated with physical conditioning of avian species from the Brazilian Cerrado - Ribeiro, Paulo Vitor Alves; Baesse, Camilla Queiroz; Tolentino, Vitor Carneiro de Magalhães; Oliveira, Marco Miguel de; Cunha, Maria Júlia Rodrigues da; Melo, Celine; Cury, Márcia Cristina (Ciência e Natura, 2022)
Blood parasites can infect myriad avian species and thereby affect the fitness and survival of their hosts. There is wide interspecific variation in parasite prevalence related to biological, ecological, and evolutionary host factors. This study aimed to determine the blood parasite prevalence in avian species from the Brazilian Cerrado and to investigate the associations among biomass, body condition, and blood parasitism. A total of 1,098 blood smears from 549 individuals (56 species) collected in four forest fragments were analyzed. Of these, 109 (19.85%) individuals from 33 species were infected: 13 (2.36%) were positive for Haemoproteus and 103 (18.76%) for Plasmodium. There was co-infection between both genera of parasites in 7 individuals. Among bird species, prevalence ranged from zero to 100%. There were significant positive correlations between prevalence and biomass and the body condition index. Hemosporid vectors track their hosts by carbon dioxide detection. Since large organisms emit more carbon dioxide, our results suggest that larger birds may be more susceptible to hemosporid vectors. Additionally, species with higher body condition indices can be more tolerant to parasites, possibly because they have more energy reserves. This study showed that species with higher biomass and body condition indices were associated with higher blood parasite prevalence, a finding that suggests these factors are efficient predictors to explain the interspecific variations. This information could be important for the understanding parasite-host relationships and useful for bird conservation programs.